2023
DOI: 10.2478/jccm-2023-0005
|View full text |Cite
|
Sign up to set email alerts
|

Early Lactate Clearance as a Determinant of Survival in Patients with Sepsis: Findings from a Low-resource Country

Abstract: Background Single lactate measurements have been reported to have prognostic significance, however, there is a lack of data in local literature from Pakistan. This study was done to determine prognostic role of lactate clearance in sepsis patients being managed in our lower-middle income country. Methods This prospective cohort study was conducted from September 2019-February 2020 at the Aga Khan University Hospital, Karachi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Since the sensitivity and specificity of a single lactate value is controversial, it has been stated that serial measurements over time or LC may be more reliable indicators [5,7]. A study found that focusing on LC rather than a single lactate level would have a more significant impact on reducing mortality [19]. Yadigaroğlu M. et al highlighted that LC levels in the 24th hour, as opposed to lactate at admission, can serve as a reliable predictor of mortality in patients with COVID-19 [6].…”
Section: Discussionmentioning
confidence: 99%
“…Since the sensitivity and specificity of a single lactate value is controversial, it has been stated that serial measurements over time or LC may be more reliable indicators [5,7]. A study found that focusing on LC rather than a single lactate level would have a more significant impact on reducing mortality [19]. Yadigaroğlu M. et al highlighted that LC levels in the 24th hour, as opposed to lactate at admission, can serve as a reliable predictor of mortality in patients with COVID-19 [6].…”
Section: Discussionmentioning
confidence: 99%
“…When the serum lactate concentration is greater than 10 mmol/L, the patient mortality rate can reach 80%, as recorded by Bai Huiying in the compilation of critical illness emergency medicine in China [3]. The medical journal compiled by Yang Mingxing shows that if severe lactic acidosis persists for 48 hours, the mortality rate can reach 100% [4]. Li et al found that blood lactate concentration is an important parameter for evaluating the prognosis of critically ill patients [5].…”
Section: Current Research Status At Home and Abroadmentioning
confidence: 99%
“…Additionally, lactate clearance is an approximate percentage of the reduction in lactate levels following early resuscitation and is a plausible method for predicting mortality [6]. Increased lactate levels correlate with poor outcomes, and survival can be predicted in critically ill adults with septic shock through early lactate clearance [7][8][9][10]. However, the predictive accuracy of lactate clearance in children with severe sepsis has not been fully investigated [4,11].…”
Section: Introductionmentioning
confidence: 99%